THE BANKING SECTOR’S PERFORMANCE IN CONDITIONS OF UNCERTAINTY - Matyrin, Andrii (Social Economics, 2025)
The purpose of the article is to analyse the reaction of the Ukrainian banking sector to uncertainty. The study identifies global (crises, conflicts, technological changes, environmental challenges) and national (annexation, military aggression) events that affect the banking sector. The dual impact of uncertainty on its activities is substantiated. The relevance of the work for Ukraine, which is facing unprecedented challenges, underlines the urgent need for such an analysis.The modern world is characterised by growing uncertainty, which has a significant impact on banks. The war in Ukraine has increased turbulence, creating new risks for liquidity, capitalisation and profitability. The article analyses the performance indicators of the banking sector of Ukraine for 2008-2025. The dynamics of lending activities, fundraising, efficiency and asset quality (profitability, share of non-performing loans) are considered. It is determined that uncertainty generates both threats (increased credit risks, market volatility, liquidity problems, cyber threats, capital outflows, panic of depositors) and opportunities (innovations, new products, non-traditional sources of income, more effective risk management, social responsibility, market consolidation).The analysis showed that the most difficult period for banks was in 2014-2017, coinciding with military aggression and annexation. This period was characterised by a drop in lending, deteriorating financial performance (negative profitability) and an increase in the share of non-performing loans, which indicates that management was unprepared. However, in 2018-2024, the banking sector is showing a steady recovery despite the pandemic and full-scale war. There has been a steady increase in deposits, indicating growing confidence and an expanding resource base. Lending had a slight upward trajectory with a decrease in the years of significant events, while investments in securities show a steady upward trend. Return on assets and equity quickly recovered to positive levels. The share of non-performing loans, having reached its peak, has been steadily declining and improved as of the end of 2024, despite the war. This indicates that banks are working with non-performing assets and improving the quality of new loans. The ability of the banking system to adapt to shocks is crucial for maintaining economic stability. Positive indicators may be the result of effective risk management.Further research will include building an economic-mathematical model to quantify the relationship between banking sector efficiency and uncertainty, which will allow for the analysis of dynamic processes and the development of more accurate forecasts.